2002
DOI: 10.1002/anie.200290038
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Total Synthesis of Mucocin, an Antitumor Agent

Abstract: Mucocin (1) is a representative annonaceous acetogenin [1] having a tetrahydropyran (THP) and a tetrahydrofuran (THF) ring. [2] This novel type of acetogenin is known to show remarkable inhibitory activities against A-549 (lung cancer) and PACA-2 (pancreatic cancer) solid tumor lines with a potency of more than 10 000 times that of adriamycin. The powerful antitumor activity and the unique structure of 1 have consequently stimulated synthetic efforts, [3] and quite recently three research groups (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…however, research on the inhibition of acetogenins against pol and topo activities is limited, probably due to the small quantities of natural products. Since the total synthesis of bioactive acetogenins, such as compound 5, is possible (17)(18)(19)(20)(21)(22)(23)(24)(25), these compounds should be provided and studied in pharmaceutical research throughout the world. compound 5 directly inhibited animal pol and human topo activities (table ii), but did not bind to dna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…however, research on the inhibition of acetogenins against pol and topo activities is limited, probably due to the small quantities of natural products. Since the total synthesis of bioactive acetogenins, such as compound 5, is possible (17)(18)(19)(20)(21)(22)(23)(24)(25), these compounds should be provided and studied in pharmaceutical research throughout the world. compound 5 directly inhibited animal pol and human topo activities (table ii), but did not bind to dna.…”
Section: Discussionmentioning
confidence: 99%
“…1) was achieved (17)(18)(19)(20)(21)(22)(23)(24)(25). Since mclaughlin et al and mata et al reported that some acetogenins have cytotoxicity against human cancer cell lines (4-7), the purpose of this review is to investigate the biochemical action of the compounds against dna metabolic enzymes such as pols and topos, and to use the compound as an antineoplastic agent.…”
Section: Introductionmentioning
confidence: 99%
“…14). 47 Treatment of dialdehyde 103 with SmI 2 at –5 °C afforded THP 104 in 87% yield. Interestingly, the other aldehyde group in 103 survives the reducing conditions.…”
Section: Application To the Synthesis Of Natural Productsmentioning
confidence: 99%
“…In 2002, the group of Takahashi and Nakata reported the total synthesis of 475 based on the SmI 2 -induced reductive cyclization as a key step ( Scheme 71 ) [ 150 ]. The THP ring in the central core 494 was constructed from 493 by the SmI 2 -induced reductive cyclization, whereas the trans -THF ring was synthesized by oxidative cyclization of a homoallylic alcohol.…”
Section: Reviewmentioning
confidence: 99%